Effects of Banana Peel Meal on the Feed Conversion Ratio and Blood Lipid Profile of Broiler Chickens - Haryanto , Aris; Miharja, Kandita; Wijayanti, Nastiti (International Journal of Poultry Science, 2015)
The aim of this research was to study the effect of banana peel meal on the feed conversion ratio (FCR) and blood lipid profile, including total cholesterol, triglycerides, high density lipoprotein (HDL and low density lipoprotein (LDL levels, in the blood serum of broiler chickens. This study used 50-day-old strains of Charoen Phokphand 707 chickens of varied sex and standard body weight. The chickens were randomly divided into five groups: control chickens were fed 100% BR-1 commercial broiler feed; treatment group 1 (P-1) was fed 90% BR-1+10% banana peel meal; P-2 was fed 80% BR-1+20% banana peel meal; P-3 was fed 70% BR-1+30% banana peel meal; P-4 was fed 60% BR-1+40% banana peel meal. After a 35-d rearing period, body weight, FCR, total cholesterol, triglyceride, HDL and LDL levels in sera were quantified and analyzed by ANOVA. The results showed that FCR, total cholesterol and LDL levels were not significantly different (p>0.05) after administration of banana peel meal, while HDL and triglyceride levels were significantly different (p